Estimating the price at which hepatitis C treatment with direct-acting antivirals would be cost-saving in Japan - Zhuo, Yueran (Sci Rep, 2020)
In Japan, 1.5–2 million people are chronically infected with hepatitis C virus (HCV) infection. New direct-acting antiviral agents (DAA) offer an unprecedented opportunity to cure HCV. While the price of HCV treatment decreased recently in most countries, it remains one of the highest in Japan. Our objective was to evaluate the cost-effectiveness of HCV treatment in patients of different age groups and to estimate the price at which DAAs become cost-saving in Japan. A previously developed microsimulation model was adapted to the Japanese population and updated with Japan-specific health utilities and costs. Our model showed that compared with no treatment, the incremental cost-effectiveness ratio (ICER) of DAAs at a price USD 41,046 per treatment was USD 9,080 per quality-adjusted life year (QALY) gained in 60-year-old patients. HCV treatment became cost-effective after 9 years of starting treatment. However, if the price of DAAs is reduced by 55–85% (USD 6,730 to 17,720), HCV treatment would be cost-saving within a 5 to 20-year time horizon, which should serve to increase the uptake of DAA-based HCV treatment. The payers of health care in Japan could examine ways to procure DAAs at a price where they would be cost-saving.